Cutaneous Wound Healing Activity of Herbal Ointment containing Tetrapleura tetraptera Fruit Extract - Otimanam, Hilary; Tologbonse, Adedayo A.; Onwuka, Ngozi A.; Usen, Wisdom (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Phytochemicals are known to possess many wounds healing properties. Phytochemicals are known to be used to protect humans against similar threat to haemostatis. To confirm this statement, wound excision measuring about 170mm was created on the back of each healthy male Albino wistar rat of same age group. They were 30 rats in all divided into 5 groups of six rats each (n=6). Three different concentrations of Tetrapleura tetraptera fruit aqueous extract were prepared (2.5g/2qg, 5.0g/20 and 10.0g/20g) of white petroleum jelly as base were used as test drugs, while gentamycin 1% ointment was used as standard drug, while the control group receive no medication. Skin irritation was determined. The ointment was applied topically on wounded areas which was measured every two days interval until full epithelialization and complete closure. Topical application of the aqueous extract of Tetrapleura tetraptera fruit ointment showed significant wound healing rate (p<0.05) and reduced epithelialization period which as also increased in dose dependent manner. Application of ointment batch containing T. tetraptera fruits extract 10.0g/20g ointment showed highest rate of wound closure with reduction in epithalization period within 14 days. Tetrapleura tetraptera fruit extract wound dressing material showed great promise and potential of the plant in treating wounds that have defied all surgical and medical interventions.